QUALITY CONTROL ASSESSMENT OF LOCALLY MANUFACTURED ASPIRIN TABLETS IN COMPARISON TO GLOBALLY PRODUCED GENERICS - HIBAH M. ALDAWSARI,; GIHAN S. LABIB, (International Journal of Pharma and Bio Sciences, 2015)
Challenges confronting the locally manufactured medications in Saudi Arabia have been increasing in the last decade. The Saudi market is mainly built on imported medications. Meanwhile, local manufacturers are much neglected in the Saudi's market. Building consumer's trust for local medication is one of the main targets to achieve success in decreasing the rate of importing medication while increasing locally produced ones. This study aims to compare the quality of some of the marketed low dose enteric coated Aspirin tablets (as a model product) produced by local Saudi pharmaceutical companies (F1 and F3) with others manufactured by an Arabian Emirate company (F5), and two other brands of USA companies (F2 and F4) as global generics. F2 represents the proprietary product produced by Bayer (Bayer Aspirin ®), to which all other brands were compared. Different quality control tests adopted by the United States Pharmacopeia and/or the British Pharmacopeia were applied to the five brands. Tablets were also assessed for physical and organoleptic properties. Results revealed that nearly all of the tested tablets met the requirements of the quality control tests adopted. This reflects their equivalency both pharmaceutically and statistically.